Molecular dynamics and integral equation study of the structure and dynamics of solid and liquid magnesium phosphide - Aydin, Yenal; Gunay, Seckin D.; Akdere, Unsal; Tasseven, Cetin (TAYLOR & FRANCIS LTD, 2024)
The static structure and self-ionic transport in solid and molten magnesium phosphide (Mg3P2) are investigated by means of the molecular dynamics simulation and the hypernetted-chain theory of liquids using a newly developed semiempirical pairwise potential. Parameters of the potential were fitted to the lattice constant and bulk modulus, and then it was tested in NVE ensemble simulation at 300 K at which X-ray powder diffraction pattern was correctly reproduced. The static structure and the dynamics of self-ion transport were investigated in NPT simulations between 300 and 1500 K. The temperature evolution of the radial distribution functions, coordination numbers, mean square displacements, self-diffusion coefficients and solid-liquid transition were established at solid and liquid phases that will be informative for the thermoelectronic, optoelectronic and energy storage applications of the magnesium phosphide.
Keywords: Magnesium phosphide; model potential; static and dynamic properties; molecular dynamics simulation; hypernetted-chain theory; PROGRAM; BI; Chemistry; Physics